Habilidade auditiva em criança desnutrida - Caldas, Patrícia Andréia [UNESP]; Giacheti, Célia Maria [UNESP]; Capellini, Simone Aparecida [UNESP] (Academia Brasileira de Audiologia, 2014)
PurposeTo characterize and compare the performance of malnourished children and normal children in auditory processing. MethodThe sample comprised 30 children from five to ten years old, both genders, being 15 malnourished children (G1) and 15 children with adequate nutritional status, as a control group (G2). The groups were paired according to gender, age and grade level. Both groups underwent peripheral and central auditory assessment, noting that malnourished children had higher changes in the skill of sequencing score for verbal and nonverbal when compared to normal children, and the same occurred in closing skills and background figure. ResultRegarding the degree of auditory processing disorder, it was more severe in malnourished children. ConclusionChildren with malnutrition have higher frequency alterations in auditory abilities when compared to normal children, being the temporal ordering skills, auditory memory, selective attention, figure-ground and closing the most affected skills.

Objetivo: Caracterizar e comparar o desempenho de crianças com desnutrição e crianças eutróficas nas habilidades do processamento auditivo. Métodos: A amostra foi composta por 30 crianças na faixa etária de 5 a 10 anos, de ambos os gêneros, sendo 15 crianças com desnutrição, que compuseram o grupo amostral (G1) e 15 crianças com estado nutricional adequado, como grupo controle (G2). Os grupos foram pareados segundo gênero, faixa etária e escolaridade. Ambos os grupos foram submetidos à avaliação auditiva periférica e central. Resultados: As crianças desnutridas apresentaram maior índice de alterações na habilidade de sequencialização sonora para sons verbais e não verbais, quando comparadas com as crianças eutróficas. O mesmo ocorreu nas habilidades de fechamento e figura fundo. Quanto ao grau do distúrbio do processamento auditivo, houve maior severidade nas crianças desnutridas. Conclusão: Crianças com desnutrição apresentaram maior frequência de alterações nas habilidades auditivas, quando comparadas a crianças eutróficas, sendo as habilidades de ordenação temporal, memória auditiva, atenção seletiva, figura fundo e fechamento, as habilidades mais afetadas.
Auditory ability in malnourished child
Keywords: Desnutrição; Audição; Percepção auditiva; Transtornos da percepção auditiva; Transtornos da audição; Malnutrition; Hearing; Auditory perception; Auditory perceptual disorders; Hearing disorders